METODE SARISWARA SEBAGAI AKOMODASI KEBERAGAMAN SISWA DI KELAS INKLUSIF - Salsabila, Hanun; Raspati, Matis Iga; Annisa, Firyalina Yulma; Andini, Dinar Westri; Praheto, Biya Ebi (Universitas Sarjanawiyata Tamansiswa, 2021)
In reality, teachers face the diversity of student characteristics in the classroom. Differences in student characteristics should be greeted with a positive attitude and emphasize that differences become a strength, not a burden. However, the reality in the field is that class differences still create gaps and are often ignored, these learning activities does not yet include every student’s participation to actively learn together in the same classroom setting. The purpose of this study is to describe the steps to apply the Sariswara method as accommodation in a diverse, inclusive classroom. The research method utilized is a literature review which contains descriptions of theories, findings, and other research materials obtained from reference to be used as a basis for research activities. This article examines the analysis of the diversity of student characteristics, learning accommodation in inclusive classrooms, and the inheritance method as an alternative solution that can be applied in the classroom to meet the learning needs of the diverse characteristics of students in the classroom.